INTERPRETATION OF DERADICALIZATION POLEMIC IN INDONESIA - Munandar, R. Aries; Syauqillah, Muhamad; Priyanto, Sapto (UI Scholars Hub, 2021)
The development of terrorism acts in parts of the world, creating geopolitical dynamics globally. The act of terrorism is clearly a threat that cannot be denied by various countries in the world. In addressing this, countries around the world are vying for an answer to solve the problem, including in Indonesia. One of the programs that is felt to be necessary is the deradicalization program against terrorism convicts. But it turns out that in the dynamics of its implementation reaps many pros and cons. This paper presents a systematic and logical argument in understanding the polemics that occur regarding the implementation of deradicalization in Indonesia. Thus, creating recommendations that can be an alternative, to be able to deal with terrorism convicts in Indonesia.